2021
DOI: 10.1021/acsenergylett.1c01563
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling the Driving Force and the Barrier to Charge Separation in Donor–Nonfullerene Acceptor Films

Abstract: We investigate the dependence of charge yields on the driving force for photoinduced electron transfer in a series of all-small-molecule, semiconducting films made from indacenodithiophene nonfullerene acceptors (IDT NFAs). In contrast to reports of efficient, barrierless charge separation at near zero driving force for NFA-containing organic photovoltaics, we find that barrierless charge separation occurs only if the driving force is sufficient to overcome the Coulomb potential, ≥300 meV, based on time-resolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…Apart from providing the power for CTEs dissociation, built‐in electric field is also responsible for the excitons diffusion and carriers transport to the corresponding electrode for collection and to avoid recombination [17] . However, in the OSCs, built‐in electric field is too small to provide sufficient driving for SEs and CTEs to split completely, or for the free charges generated by separation to migrate quickly, resulting in the charges captured in the traps or accumulated at the interfaces [18] . Such suboptimal charge dynamics normally causes a pronounced non‐radiative recombination of charges or excitons, which has been identified as the main energy loss ( E loss ) limiting the photovoltaic efficiency of OSCs [19, 20] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from providing the power for CTEs dissociation, built‐in electric field is also responsible for the excitons diffusion and carriers transport to the corresponding electrode for collection and to avoid recombination [17] . However, in the OSCs, built‐in electric field is too small to provide sufficient driving for SEs and CTEs to split completely, or for the free charges generated by separation to migrate quickly, resulting in the charges captured in the traps or accumulated at the interfaces [18] . Such suboptimal charge dynamics normally causes a pronounced non‐radiative recombination of charges or excitons, which has been identified as the main energy loss ( E loss ) limiting the photovoltaic efficiency of OSCs [19, 20] .…”
Section: Introductionmentioning
confidence: 99%
“…[17] However, in the OSCs, built-in electric field is too small to provide sufficient driving for SEs and CTEs to split completely, or for the free charges generated by separation to migrate quickly, resulting in the charges captured in the traps or accumulated at the interfaces. [18] Such suboptimal charge dynamics normally causes a pronounced non-radiative recombination of charges or excitons, which has been identified as the main energy loss (E loss ) limiting the photovoltaic efficiency of OSCs. [19,20] Nevertheless, strengthening the built-in electric field to promote exciton separation and transport, and reduce the nonradiative recombination, is of great significance to improve the PCE of the OSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from providing the power for CTEs dissociation, built‐in electric field is also responsible for the excitons diffusion and carriers transport to the corresponding electrode for collection and to avoid recombination [17] . However, in the OSCs, built‐in electric field is too small to provide sufficient driving for SEs and CTEs to split completely, or for the free charges generated by separation to migrate quickly, resulting in the charges captured in the traps or accumulated at the interfaces [18] . Such suboptimal charge dynamics normally causes a pronounced non‐radiative recombination of charges or excitons, which has been identified as the main energy loss ( E loss ) limiting the photovoltaic efficiency of OSCs [19, 20] .…”
Section: Introductionmentioning
confidence: 99%
“…These studies revealed that the barrierless charge separation occurs only if the driving force is sufficient to overcome the Coulomb potential. 26 The recent advancements in utilizing the excitedstate energy transfer for enhanced light energy conversion demonstrate its potential as an emergent strategy to realize artificial photosynthetic mimics.…”
mentioning
confidence: 99%
“…Reid, Rumbles, and co-workers investigated the dependence of charge yields on the driving force for photoinduced electron transfer in indaceno­dithiophene NFA-based semiconducting films. These studies revealed that the barrierless charge separation occurs only if the driving force is sufficient to overcome the Coulomb potential . The recent advancements in utilizing the excited-state energy transfer for enhanced light energy conversion demonstrate its potential as an emergent strategy to realize artificial photosynthetic mimics.…”
mentioning
confidence: 99%